2012
DOI: 10.3390/rs4113444
|View full text |Cite
|
Sign up to set email alerts
|

A Geospatial Appraisal of Ecological and Geomorphic Change on Diego Garcia Atoll, Chagos Islands (British Indian OceanTerritory)

Abstract: This study compiled a wide range of modern and historic geospatial datasets to examine ecological and geomorphic change at Diego Garcia Atoll across a 38-year period . This remarkable collection of spatially referenced information offered an opportunity to advance our understanding of the nature and extent of environmental change that has taken place with the construction of the military airbase at Diego Garcia. Changes assessed included movements of the lagoon rim shorelines, changes in the terrestrial vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…The remaining four photo records suggested no shoreline change, but our measurements suggested that rim widths had eroded over the longer 38-year period. Thus, our study [2] appears to indicate a greater amount of erosion than Sheppard's photographic evidence. Indeed, the wider study reported both erosion and accretion across 26 and 43 OPEN ACCESS transects respectively.…”
Section: Received: 13 March 2014 / Accepted: 17 March 2014 / Publishecontrasting
confidence: 47%
See 4 more Smart Citations
“…The remaining four photo records suggested no shoreline change, but our measurements suggested that rim widths had eroded over the longer 38-year period. Thus, our study [2] appears to indicate a greater amount of erosion than Sheppard's photographic evidence. Indeed, the wider study reported both erosion and accretion across 26 and 43 OPEN ACCESS transects respectively.…”
Section: Received: 13 March 2014 / Accepted: 17 March 2014 / Publishecontrasting
confidence: 47%
“…Sheppard provided eight independent photorecords of his inter-annual observations for inclusion in our study ([3]) with which moderate correspondence was found when compared to our findings [2]. Four photographs exhibiting erosion were also associated with erosion in analysis of rim width transects.…”
mentioning
confidence: 84%
See 3 more Smart Citations